Acquired amegakaryocytic thrombocytopenic purpura progressing into aplastic anemia - Novotný, Jan Philipp; Köhler, Birgit; Max, Regina; Egerer, Gerlinde (Prague Medical Report, 2017)
Acquired amegakaryocytic thrombocytopenic purpura (AATP) is a rare hematological disorder characterized by severe thrombocytopenia and a complete or near-to complete absence of megakaryocytes in the bone marrow, while granulopoiesis, as well as erythropoiesis are usually preserved. Although autoimmune mechanisms are believed to be causative, the exact underlying pathogenesis is not known. To date, only few cases have been reported and management of this disease remains controversial with immunosuppression being the treatment modality of choice in the majority of patients. In this article, we report a case of newly acquired AATP without an associated autoimmune disease, refractory to corticoids, intravenous immunoglobulin (IVIG) and second-generation TPO (thrombopoietin) agonists, which have recently been approved for the treatment of thrombocytopenia. Finally, in accordance with other reports, disease progression into aplastic anemia has occurred.
Keywords: Middle Aged; aplastická anemie; lidé středního věku; lidé; trombocytopenická purpura; Anemia, Aplastic; mužské pohlaví; Immunosuppressive Agents; Male; antibakteriální látky; Anti-Bacterial Agents; Purpura, Thrombocytopenic; imunosupresiva; Treatment Outcome; výsledek terapie; Humans